2006
DOI: 10.1158/1078-0432.ccr-06-1393
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anticancer Effect of Thalidomide: Inhibition of Intercellular Adhesion Molecule-1–Mediated Cell Invasion and Metastasis through Suppression of Nuclear Factor-κB

Abstract: Purpose: Thalidomide has been reported to have antiangiogenic and antimetastatic effects.Intercellular adhesion molecule-1 (ICAM-1) was shown to be involved in monocyte adherence to epithelial cells and cancer cell invasion. In this study, we further investigated the role of ICAM-1 in tumorigenesis, including tumor formation and metastasis. ICAM-1 as a molecular target for cancer and the anticancer effect of thalidomide were investigated. Experimental Design: Expression of ICAM-1 protein in human lung cancer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
2
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 39 publications
(34 reference statements)
3
103
2
11
Order By: Relevance
“…Our findings are consistent with experimental studies which have demonstrated that statins promote apoptosis and limit proliferation in EAC cell lines [5][6][7][8] 6 , an adhesion molecule involved in trans-endothelial tumour cell migration and metastatic spread 23,24 . Whether these mechanisms operate to explain the associations observed in this study is not clear.…”
Section: Biological Mechanismssupporting
confidence: 91%
“…Our findings are consistent with experimental studies which have demonstrated that statins promote apoptosis and limit proliferation in EAC cell lines [5][6][7][8] 6 , an adhesion molecule involved in trans-endothelial tumour cell migration and metastatic spread 23,24 . Whether these mechanisms operate to explain the associations observed in this study is not clear.…”
Section: Biological Mechanismssupporting
confidence: 91%
“…36 It has been reported that the expression of VEGF and/or ICAM-1 is correlated to the malignancy, or metastatic potential of tumors including osteosarcoma. 37,38 In our study, the mRNA levels of VEGF and ICAM-1 were significantly decreased by transfection of NF-kB decoy ODN, indicating that the metastatic potential of LM8 cells was decreased by the transfection of NF-kB decoy ODN.…”
Section: Discussionsupporting
confidence: 50%
“…Indeed, thalidomide, which also acts on CD54 is used in myeloma patients and has efficacy in lung tumors xenografted in mice. 55 Furthermore, many cancer patients are already immunosuppressed from their disease. Therefore, the predicted immunosuppressive activity of UV3 does not preclude its testing in Phase I clinical trials, where immunosuppression and other side effects are best determined during a dose escalation.…”
Section: Discussionmentioning
confidence: 99%